2014
DOI: 10.5935/0004-2749.20140053
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable sutures in strabismus surgery: why surgeons either love them or hate them after three decades

Abstract: Strabismus surgeons continually seek to achieve the best results from their surgery, which means stable motor alignment and sensory improvement with a minimum number of procedures (1) . But the tables and algorithms that we employ for the number of muscles to be included in the surgery, and for the doses of surgery, are often not appropriate for difficult or unpredictable cases (2) . The ability to modify the site of the muscle insertion on the globe to refine surgical results and to control postoperative devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…They also point out that the adjustment procedure is uncomfortable and stressful for the patient and requires special nursing care [5]. Interestingly, Vassconcelos and Guyton in their editorial for Arquivos Brasilerios de Oftalmologia indicated that the adoption of AS in strabismus surgery is partly related to surgical experience [6]. Successful use of AS requires a long apprenticeship and often promotes a high load of stress at the beginning of the learning curve, so some surgeons favor the simpler NAS technique.…”
Section: Introductionmentioning
confidence: 99%
“…They also point out that the adjustment procedure is uncomfortable and stressful for the patient and requires special nursing care [5]. Interestingly, Vassconcelos and Guyton in their editorial for Arquivos Brasilerios de Oftalmologia indicated that the adoption of AS in strabismus surgery is partly related to surgical experience [6]. Successful use of AS requires a long apprenticeship and often promotes a high load of stress at the beginning of the learning curve, so some surgeons favor the simpler NAS technique.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, surgeons may be reluctant to incorporate adjustable suture techniques because of the additional surgical and postoperative investment of time and resources. 4,5 Despite this uncertainty, there have been advances in the technique of adjustable suture placement that have expanded its use and applicability. 6 Modifications in the suture technique allow for the possibility of delayed suture adjustment within 1 week of surgery.…”
Section: Introductionmentioning
confidence: 99%